The Process of Iranian Cultural Identity Formation in Interaction with Islam: A Historical Review - Taheri, Ahmad Reza; Shahrokhi, Seyed Alaeddin; Salah, Mehdi; Razavi, Seyed Abolfazl (Universitas Negeri Yogyakarta, 2023)
This paper is inspired by the hypothesis of the